SEPIC for solar energy–based sensorless speed control of induction motor drive. (20th October 2021) - Sharma, Shailendra Kumar; Pardhi, Pemendra Kumar; Saxena, Rakesh
Summary: This article presents a single‐ended primary inductor converter (SEPIC) for solar energy–based sensorless speed control of squirrel cage induction motor (SCIM) drive. In the sensorless speed control, actual rotor speed estimation is done using accurate stator and rotor flux estimation using sensed SCIM terminal voltages and currents. The SEPIC is employed in between solar photovoltaic (PV) panel and DC link of three‐phase voltage source inverter (VSI). The SEPIC is controlled to extract maximum PV power. The control of SEPIC is obtained using the fuzzy logic–based maximum power point tracking (MPPT) algorithm. The effectiveness of the proposed system and its control is validated on developed laboratory prototype using Texas LaunchPad TMS320F28379D microcontroller. Abstract : This article deals with single‐ended primary inductor converter (SEPIC) for solar energy–based sensorless speed control of induction motor drive for autonomous application; the significant contributions in this article are, The control of SEPIC is obtained using fuzzy logic control (FLC). The FLC provides fast dynamic response under change in environment conditions and offers reduced oscillations in PV voltage and power. Solar power–driven speed sensorless control of squirrel cage induction motor (SCIM) drive is proposed. The speed sensorless control helps in cost minimization and improves reliability of autonomous drive system due to reduction in sensor count. A discrete moving average–based dc offset rejection concept is developed and implemented on low cost microcontroller, that is, TMS320F28379D. It helps in obtaining accurate flux for estimating the speed of the SCIM. The state space model of SEPIC is obtained to determine transfer function to ensure stability under required operating conditions. Prototype of the proposed solar energy–driven SCIM drive is developed in laboratory to analyze its performance.